2017
DOI: 10.1162/jocn_a_01059
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Probe Similarity on Retrieval and Comparison Processes in Associative Recognition

Abstract: In this study, we investigated the information processing stages underlying associative recognition. We recorded EEG data while participants performed a task that involved deciding whether a probe word triple matched any previously studied triple. We varied the similarity between probes and studied triples. According to a model of associative recognition developed in the Adaptive Control of Thought-Rational cognitive architecture, probe similarity affects the duration of the retrieval stage: Retrieval is faste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 42 publications
4
27
0
Order By: Relevance
“…Based on a different EEG experiment, Zhang et al . () hypothesized that in this stage the words that are on the screen are compared to a pair (or triplet in this experiment) retrieved from memory, word by word. Additionally, MEG data have shown that word pairs were retrieved from temporal regions and subsequently represented pre‐frontally, while the comparison itself was associated with activation in the parietal cortex (Borst et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on a different EEG experiment, Zhang et al . () hypothesized that in this stage the words that are on the screen are compared to a pair (or triplet in this experiment) retrieved from memory, word by word. Additionally, MEG data have shown that word pairs were retrieved from temporal regions and subsequently represented pre‐frontally, while the comparison itself was associated with activation in the parietal cortex (Borst et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The last two stages correspond to the Mapping stage and the Response stage described in the process model, as one needs to select and execute a motor response at the end of each trial. The Preattention stage, the Encoding stage, and the Response stage were also identified in previous studies using an associative recognition task (Anderson et al 2016;Zhang et al 2017). The longer-duration Mapping stage, during which subjects prepare motor response by mapping two digits to the corresponding key presses, was not required in our earlier tasks where participants simply made a yes/no response.…”
Section: Identifying the Stage Durations And The Bump Profiles In Hsmmentioning
confidence: 78%
“…recovering the durations of the underlying processing stages (e.g., recollection, decision) and showed predictable changes with experimental factors (Anderson et al 2016;Walsh et al 2017;Zhang et al 2017Zhang et al , 2018. The HSMM-MVPA method identifies brief, distinctive profiles of scalp activity (i.e., bumps) at variable latencies in each trial (Anderson et al 2016).…”
Section: Hsmm-mvpa Applied To Eegmentioning
confidence: 99%
“…There is also a recent line of research focused on constructing fully analytic ACT-R models (Said et al, 2016), which could allow more efficient parameter inference using, for example, gradient-based methods. Some recent ACT-R studies have also used neuroimaging data to isolate active mental stages during task completion and used these measurements to infer specific model parameters (Anderson & Fincham, 2014a;Zhang, Walsh, & Anderson, 2016).…”
Section: Traditional Parameter Inferencementioning
confidence: 99%